KEBIJAKAN LUAR NEGERI KOREA UTARA DIBAWAH KEPEMIMPINAN KIM JONG UN DALAM PROLIFERASI NUKLIR TERHADAP KOREA SELATAN TAHUN 2013-2015 - Putra, Andika Fajar Pratama; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research describes foreign policy North Korea under the leadership of kim jong un in nuclear proliferation of against South Korea in 2013-2015. To described diplomatic relations between South Korea with North Korea. To know the explanation of the escalation conflict North Korea with South Korea under leadership Kim Jong Un. The theories applied is Behaviorism, philosophy in psychology based on a proposition that all done organisms including the act of the mind, or feeling can and has to be considered as behavior. In this analogy individual it is through intellectual a series of stages, by applying of reasoning that earnestly seek to assign choice of the policy. The conclusion of this research are the policy South Korea in the safety and weaponry certainly had the purpose of protect and to secure the defense and the security of his country from the threat of North Korean nuclear attack. This policy is one of embodiment of thought security dilemma who which an attempt South Korea in increase ordnance and security was evidence fear South Korea related to the progress of North Korean nuclear. Leadership Kim Jong Un in nuclear proliferation against it south is for self-defense by issuing policy self defense by national security the state North Korea.Key words: foreign policy, nuclear, North Korea, South Korea, Kim Jong Un